Pharmacological treatment in autism: a proposal for guidelines on common co-occurring psychiatric symptoms - Mariah A. Manter; Kirstin B. Birtwell; James Bath; Nora D. B. Friedman; Christopher J. Keary; Ann M. Neumeyer; Michelle L. Palumbo; Robyn P. Thom; Emily Stonestreet; Hannah Brooks; Kelly Dakin; Jacob M. Hooker; et al. (BMC Medicine)
Abstract Background The prevalence of autism spectrum disorder (ASD) has surged, with an estimated 1 in 36 eight-year-olds in the United States meeting criteria for ASD in 2020. Autistic individuals face elevated rates of co-occurring medical, psychiatric, and behavioral conditions compared to non-autistic individuals. The rising ASD-patient demand is increasingly outpacing the capacity of ASD-specialty clinics, resulting in urgent need for autism-competent providers in general practice settings. This work aims to empower healthcare providers, especially primary care providers (PCPs), with guidelines for the recognition and safe pharmacologic management of common co-occurring psychiatric and behavioral conditions in ASD. Methods Lurie Center for Autism medical providers, who have extensive experience in ASD care, delineated approaches for recognition and pharmacological treatment of sleep disturbances, attention-deficit/hyperactivity disorder (ADHD), anxiety, depression, and irritability tailored to ASD patients. Pharmacological guidelines were iteratively refined until consensus was reached. Treatment differences relative to standard of care (SOC) of non-autistic individuals are noted. Key literature and clinical trial results were reviewed to supplement clinical experience. Results The pharmacological treatment pathways reflect how appropriate medication options for ASD patients can depend on many factors unique to the patient and can differ from established non-autistic SOC. Key takeaways include: For sleep disturbances in ASD, initial strategies align with non-autistic SOC, emphasizing sleep hygiene and melatonin use. First-line recommendations for treating ADHD, anxiety, and depression in ASD differ from non-autistic SOC; α2-adrenergic agonists are more suitable than stimulants for some ASD-ADHD patients, buspirone and mirtazapine are preferred to selective serotonin reuptake inhibitors (SSRIs) for anxiety, and duloxetine, mirtazapine, bupropion, and vortioxetine are recommended ahead of SSRIs for depression. Addressing irritability in ASD requires interdisciplinary evaluation of contributing factors, and guanfacine, risperidone, or aripiprazole may be appropriate, depending on severity. Conclusions Recognition and treatment of co-occurring psychiatric and behavioral conditions in autistic patients must account for differences in clinical presentation and medication effectiveness and tolerability. Drawing on evidence-based clinical insights, these guidelines seek to support PCPs in making informed decisions when prescribing medications for ASD patients with co-occurring psychiatric and behavioral conditions, ultimately enhancing access to timely, comprehensive care for all individuals with ASD.